2021
DOI: 10.3390/nu13103442
|View full text |Cite
|
Sign up to set email alerts
|

Monitored Supplementation of Vitamin D in Preterm Infants: A Randomized Controlled Trial

Alicja Kołodziejczyk-Nowotarska,
Renata Bokiniec,
Joanna Seliga-Siwecka

Abstract: Appropriate supplementation of vitamin D can affect infections, allergy, and mental and behavioral development. This study aimed to assess the effectiveness of monitored vitamin D supplementation in a population of preterm infants. 109 preterm infants (24 0/7–32 6/7 weeks of gestation) were randomized to receive 500 IU vitamin D standard therapy (n = 55; approximately 800–1000 IU from combined sources) or monitored therapy (n = 54; with an option of dose modification). 25-hydroxyvitamin D [25(OH)D] concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Data from the present study indicate that an increase in vitamin D supplementation and detailed recommendations for regular monitoring during the first year of life are necessary. Recent studies already show promising improvement using adjusted vitamin D supplementation [ 31 , 32 ]. Artman et al went up to 800 IE/day in infants with low serum 25-OH-vitamin D levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the present study indicate that an increase in vitamin D supplementation and detailed recommendations for regular monitoring during the first year of life are necessary. Recent studies already show promising improvement using adjusted vitamin D supplementation [ 31 , 32 ]. Artman et al went up to 800 IE/day in infants with low serum 25-OH-vitamin D levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study reported that 19% of preterm infants still had 25(OH)D levels of >125nmol/L at 34-37 weeks of corrected age after dose adjustments. 5 Despite this, we chose monthly monitoring with standardised adjustments. The multinomial analysis did not find any significant associations, probably due to the cohort's size and heterogeneity.…”
Section: Laborie Etmentioning
confidence: 99%
“…Interestingly, a previous study reported that 19% of preterm infants still had 25(OH)D levels of >125nmol/L at 34–37 weeks of corrected age after dose adjustments 5 . Despite this, we chose monthly monitoring with standardised adjustments.…”
Section: (Oh)d Level P Values* Low N = 13 Normal N = 73 High N = 13mentioning
confidence: 99%
“…Many studies on preterm infants have compared responses to different levels of vitamin D supplementation with these guidelines in mind. The results have suggested supplementation levels of 800 to 1000 IU per day, but, above all, they have stressed the need to monitor 25‐hydroxy vitamin D level (25(OH)D) monthly in preterm infants 3‐5 . Vitamin D deficiency is frequent in the general population, even in children who are routinely supplemented with vitamin D up to 18 years of age 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The results have suggested supplementation levels of 800 to 1000 IU per day, but, above all, they have stressed the need to monitor 25-hydroxy vitamin D level (25(OH)D) monthly in preterm infants. [3][4][5] Vitamin D deficiency is frequent in the general population, even in children who are routinely supplemented with vitamin D up to 18 years of age. 6 Preterm infants face a particular risk, mainly because they are dependent on maternal vitamin D status in utero, especially during the third trimester of pregnancy.…”
mentioning
confidence: 99%